Management of Atopic Dermatitis: Clinical Utility of Ruxolitinib - Owji S; Caldas SA; Ungar B (Journal of Asthma and Allergy, 2022)
Shayan Owji,1,2 Stella A Caldas,1,3 Benjamin Ungar1 1Department of Dermatology, Icahn School of Medicine at Mount Sinai, New York, NY, USA; 2The University of Texas Medical Branch, Galveston, TX, USA; 3George Washington School of Medicine and Health Sciences, Washington, DC, USACorrespondence: Benjamin Ungar, Department of Dermatology, Icahn School of Medicine at Mount Sinai, 5 E. 98th St. Fifth Floor, New York, NY, USA, Tel +1 413-424-9551, Email Benjamin.ungar@mountsinai.orgAbstract: Atopic dermatitis (AD) is a common chronic, pruritic inflammatory skin disease that profoundly impacts patients’ quality of life. As the first FDA-approved topical JAK inhibitor, ruxolitinib 1.5% cream represents a novel therapeutic topical agent for the treatment of AD. The objective of this review is to summarize the efficacy and safety of ruxolitinib cream in patients with AD based on the available evidence. Overall, ruxolitinib cream demonstrated high efficacy and a favorable safety profile for treating atopic dermatitis.Keywords: atopic dermatitis, eczema, ruxolitinib, JAK inhibitor, topical, itch